The Influence of Tax Knowledge, Tax Incentives and Digital Literacy on Sustainable MSME Performance (Case Study: MSMEs in Bengkulu City) - Anggraini, Dini; Novitasari, Novitasari (Dinasti Publisher, 2025)
This research aims to examine how digital literacy, tax incentives, and tax knowledge affect the long-term success of small and medium-sized enterprises (SMEs) in Bengkulu City. The background is the rapid growth of MSMEs in Bengkulu City which will reach 44,742 units in 2024 and the challenges of sustainability in the digital era, as well as taxation issues which are crucial factors in achieving business sustainability. The study uses Resource-Based View Theory as a conceptual basis to explain how strategic resource integration can create competitive advantage. Using the Slovin formula, we were able to calculate that there are 44,742 MSMEs in the population, and we used this information to choose 397 for our quantitative study. Data was collected using a Likert scale questionnaire, and various statistical tests, including multiple linear regression, were used to examine the findings. According to the study's findings, digital literacy and tax incentives significantly improve the performance of sustainable MSMEs, while tax knowledge does not show a significant impact. Simultaneously, the three variables affect the performance of sustainable MSMEs with a contribution of 34.2%, indicating that tax knowledge, tax incentives, and digital literacy are factors that influence the performance of sustainable MSMEs, but there is still 65.8% of the variation explained by additional elements that are not considered in this study. The limitations of this study lie in the use of paper questionnaires due to the low response to Google Form and only using three variables in the analysis. Additional tax factors that could have a bigger impact on MSME performance include tax compliance and views of tax fairness; these should be included in future studies.